(-2)2+3= -1 hope this helps you
Answer:
(-4,-3)
Step-by-step explanation:
The x value is -4 and the y value is -3
Greetings!Simplify the Expression.
Distribute the Parenthesis.
<em>How?</em><span> Multiply the terms inside the Parenthesis by the term outside of the Parenthesis.
</span>
Combine Like Terms.

The Answer Is:
![\left[\begin{array}{ccc}17\end{array}\right]](https://tex.z-dn.net/?f=%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D17%5Cend%7Barray%7D%5Cright%5D%20)
Hope this helps.
-Benjamin
Answer:
D) 4
Step-by-step explanation:
By remote interior angle property if a triangle, we have:
19x° + (18x - 4)° = 144°
(18x - 4 + 19x)° = 144°
(37x - 4)° = 144°
37x - 4 = 144
37x = 144 + 4
37x = 148
x = 148/37
x = 4